Topical application of Photofrin® for photodynamic diagnosis of malignant cutaneous neoplasms. Issue 10 (October 2018) - Lin, Yu-Te; Hsiao, Yen-Chang; Chiang, Yu-Fan; Chang, Cheng-Jen
ABSTRACT: Objectives: The prognosis of patients suffering from malignant cutaneous neoplasms can be improved by early diagnosis. Exact demarcation of tumor margins could contribute to optimum results in surgical excision and reconstruction. The purpose of our study is to evaluate Photofrin ® with a new diagnostic procedure, photodynamic diagnosis (PDD), for the detection of Bowen's disease (squamous cell carcinoma (SCC) in situ), SCC, and basal cell carcinoma (BCC). Materials and methods: Sixty patients with cutaneous neoplasms received 2.5 mg/mL Photofrin ® solution topically. After a period of 3 hours, the patients underwent fluorescence illumination (λex = 370–450 nm). Guided by their visible fluorescence, lesions were biopsied at four suspicious sites in each patient. All specimens were analyzed and measured by a pathologist. A quantitative analysis of the fluorescence contrast between the neoplasms and healthy tissue was performed using the Red, Blue, and Green (RGB) Mode and Gray Scale (GS). Statistical analysis was performed by the analysis of variance (ANOVA) test for multiple comparisons. Results: Of the 60 patients (20 Bowen's disease, 20 SCC, and 20 BCC), malignant neoplasms could be clearly distinguished from adjacent healthy tissue under fluorescence illumination ( P < 0.0001). The sensitivity of the malignant neoplasms evaluated using the RGB and GS modes combined showed 92.74% in image results. The specificity of the malignant neoplasms evaluated using the RGB and GS modes combined showed 95.77%. Conclusion: Light-induced fluorescence detection using topical Photofrin ® provides a sensitive, noninvasive technique for the early identification of malignant cutaneous neoplasms.